Advanced test on potential of bacteria symbionts seagrass Enhalus acoroides and Thalassia hemprichii as antibacterial towards disease cause agents Vibriosis - Delianis Pringgenies; Arief Dwi Kurniawan (Jurusan Akuakultur, Universitas Bangka Belitung, 2016)
This study is the further study on isolation and identification of bacterial symbionts and Enhalus acoroides and Thalassia hemprichii. The results showed that the activity of bacterial symbionts seagrass Enhalus acoroides and Thalassia hemprichii acquired seven bacterial isolates which were able to inhibit Vibrio harveyimasing - each isolate consisted of 5 Thalassia hemprichii isolates and 2 Enhalus isolates. The results of the study showed that the activity of bacterial symbionts seagrass Enhalus acoroides and Thalassia hemprichii acquired 7 bacteria isolates to inhibit Vibrio. There were 4 isolates that had bactericidal activities. Two bacterial symbionts that had the highest inhibitory zones were identified, namely Th 12 isolate, type of bacteria Bacillus macerans, meanwhile Eh 10 isolate was Micrococcus varians bacteria. The results showed that the inhibitory zone Eh 9 isolate (3.87 ± 0.25 mm) was higher than Th 20 isolate (3.14 ± 0.18 mm). Based on the results of biochemical identification of bacteria known that Eh 9 was kind of Brevibacterium sp ., while the Th 20 isolate was a type of bacteria Bacillus pumilus. The results concluded that the bacterial symbionts that comes from Enhalus acoroides and Thalassia hemprichii can serve as an antibacterial of Vibrio harveyi